Acceptance Speech for the Patriot Award - Wriston, Walter B. (Tufts Archival Research Center, 2007)
The document was created from the speech, "Acceptance Speech for the Patriot Award," written by Walter B. Wriston for the Sons of the Revolution Patriot Award Dinner on 21 February 1992. The original speech is located in MS134.001.010.00006.